The impact of involvement in the global value chain on coffee farmers in Indonesia: Case study of Margamulya Coffee Producer Cooperative and Mitra Malabar Cooperative, Bandung, Indonesia - Amzul Rifin; Dahlia Nauly (Asian Development Bank Institute (ADBI), 2020)
One of the institutions involved in coffee value chain in Indonesia is the cooperative. We compare the experience of two cooperatives in exporting coffee beans. The Margamulya Coffee Producer Cooperative currently exports coffee beans directly and through an exporter, while the Mitra Malabar Cooperative previously exported its coffee beans but currently focuses on the domestic market. Both cooperatives obtain benefits from exporting, and these benefits are transmitted to their members through the higher price and the services provided to them. Based on the experience of both cooperatives, direct export is more beneficial since a better price is charged and higher value-added coffee is sold rather than from exporting through exporters. In order to conduct direct export, cooperatives must be provided capital assistance so that they can purchase coffee beans from the farmers and build storage facilities.
Keywords: Q13; Q17; O13; 330; cooperatives; coffee beans; export